Pengaruh Strategi Konflik Kognitif Terhadap Kemampuan Representasi Matematis Siswa Kelas X SMK Negeri 1 Siabu - Ade Rizky Nasution; Nova Christina Dewi; Nurdalilah (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2025)
This study aims to examine the effect of cognitive conflict strategies on the mathematical representation ability of tenth-grade students at SMK Negeri 1 Siabu. The cognitive conflict strategy is believed to stimulate students’ active engagement through the stages of presenting conflict, creating conflict through demonstrations, and resolving it through discussion and reflection. The research employed a quasi-experimental method with a posttest-only control group design. The instruments used were a mathematical representation test and a student response questionnaire. The results showed a significant difference in mathematical representation ability between students who were taught using the cognitive conflict strategy and those who learned through conventional models. Thus, the cognitive conflict strategy is effective in improving students’ mathematical representation ability.